SMART CARE FOR DIABETES: INTEGRATING TECHNOLOGY AND LIFESTYLE FOR BETTER OUTCOMES - Aleksandra Maciejczyk; Katarzyna Krupa; Weronika Głowacz; Janusz Świeczkowski-Feiz (International Journal of Innovative Technologies in Social Science, 2025)
Diabetes mellitus remains a global health challenge, with increasing prevalence and significant complications, particularly in type 2 diabetes (T2D). Lifestyle factors such as diet, physical activity, and stress are critical in both the prevention and management of the disease. Simultaneously, medical technologies are transforming diabetes care by enabling more precise glycemic control.This review synthesizes findings from 26 studies published between 2010 and 2025, selected via structured searches of PubMed, Scopus, and Web of Science. Four independent reviewers screened the titles. The review was conducted in accordance with PRISMA 2020 guidelines.Evidence supports that dietary approaches (like low-carbohydrate, Mediterranean, and personalized nutrition) are effective in improving glycemic outcomes. Structured aerobic and resistance exercise programs are associated with significant reductions in HbA1c and improved insulin sensitivity. Stress management techniques, such as mindfulness-based interventions, offer additional psychological and metabolic benefits. CGM and insulin pump therapies, especially in hybrid closed-loop systems, significantly improve glycemic metrics and patient-reported outcomes. AI applications show promise in insulin titration and risk prediction, though integration into clinical practice requires further research.In conclusion, integrating lifestyle modifications with medical technologies offers the greatest potential for optimizing diabetes care. Future efforts should focus on personalized approaches and equitable access to advanced therapies.